The Role of Board Member Characteristics in Shaping Corporate Performance: Evidence from Indonesia - Tessa Vanina Soetanto; Catherine Ivana Rusli; Leticia Theophillia Soesilo (Master of Management, School of Business and Management, Petra Christian University, 2025)
Boards of directors have a significant impact on firm performance. With the growing emphasis on diversity, it is essential to explain how demographic diversity among leaders relates to firm performance. The paper examines the relationship between demographic diversity, age, gender, tenure, and the performance of Indonesian manufacturing firms. The writers adopt Resource Dependency Theory as the theoretical basis for this research. Although studies on board diversity exist, the influence of board diversity on manufacturing firms, which is becoming increasingly crucial in Indonesia, is rarely discussed. The writers analyzed secondary data from 2016 to 2022 using Ordinary Least Squares regression. Results show that age and tenure diversity have a positive impact on the performance of larger firms, but no effect on smaller firms. These results add practical implications for manufacturing firms seeking to enhance decision-making with diverse leadership.